Un/Certain Futures Rollen des Designs in gesellschaftlichen Transformationsprozessen - Förster, Marius; Hebert, Saskia; Hofmann, Mona; Jonas, Wolfgang (Design, 2018)
A multi-Disciplinary View at Contingent Futures - Beyond the Placative Dualism of Design versus Disaster.